Lung microbiome and host immune tone in subjects with idiopathic pulmonary fibrosis treated with inhaled interferon-γ. Issue 3 (12th July 2017) - Wang, Jing; Lesko, Melissa; Badri, Michelle H.; Kapoor, Bianca C.; Wu, Benjamin G.; Li, Yonghua; Smaldone, Gerald C.; Bonneau, Richard; Kurtz, Zachary D.; Condos, Rany; Segal, Leopoldo N.
Therapies targeting inflammation reveal inconsistent results in idiopathic pulmonary fibrosis (IPF). Aerosolised interferon (IFN)-γ has been proposed as a novel therapy. Changes in the host airway microbiome are associated with the inflammatory milieu and may be associated with disease progression. Here, we evaluate whether treatment with aerosolised IFN-γ in IPF impacts either the lower airway microbiome or the host immune phenotype. Patients with IPF who enrolled in an aerosolised IFN-γ trial underwent bronchoscopy at baseline and after 6 months. 16S rRNA sequencing of bronchoalveolar lavage fluid (BALF) was used to evaluate the lung microbiome. Biomarkers were measured by Luminex assay in plasma, BALF and BAL cell supernatant. The compPLS framework was used to evaluate associations between taxa and biomarkers. IFN-γ treatment did not change α or β diversity of the lung microbiome and few taxonomic changes occurred. While none of the biomarkers changed in plasma, there was an increase in IFN-γ and a decrease in Fit-3 ligand, IFN-α2 and interleukin-5 in BAL cell supernatant, and a decrease in tumour necrosis factor-β in BALF. Multiple correlations between microbial taxa common to the oral mucosa and host inflammatory biomarkers were found. These data suggest that the lung microbiome is independently associated with the host immune tone and may have a potential mechanistic role in IPF. Lower airway microbiome and immunological tone are associated in IPF, an effect independent of IFN-γ treatment http://ow.ly/cTDo30bsJiN